2008
DOI: 10.1017/s1368980008002826
|View full text |Cite
|
Sign up to set email alerts
|

The Asian enigma: predisposition for low adult BMI among people of South Asian descent

Abstract: Objective: To investigate the Asian enigma, the phenomenon of relatively high levels of undernutrition among children and adult women in South Asia, despite more favourable records with respect to infant mortality, women's education, food availability or other aspects of living conditions in comparison with, for example, sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…One concern with using height as a measure of malnutrition is that it may be partially determined genetically. But while some authors still argue that genetics matter (Nubé, 2007), the WHO Multi-Center Growth Reference Study has shown, through work in multiple countries, that ethnicity and genetics matter less than environmental circumstances related to child growth (see http://www.who.int/childgrowth/mgrs/en/). Moreover, long-run historical data (Cole, 2003;Deaton, 2008) verify that heights do increase with improvements in incomes, education, and healthcare, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…One concern with using height as a measure of malnutrition is that it may be partially determined genetically. But while some authors still argue that genetics matter (Nubé, 2007), the WHO Multi-Center Growth Reference Study has shown, through work in multiple countries, that ethnicity and genetics matter less than environmental circumstances related to child growth (see http://www.who.int/childgrowth/mgrs/en/). Moreover, long-run historical data (Cole, 2003;Deaton, 2008) verify that heights do increase with improvements in incomes, education, and healthcare, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In India, the prevalence of thinness/undernutrition is still the highest in the world,5 despite generally better socio-economic circumstances and lower poverty levels than in many other developing countries, a situation that has been called the ‘South Asian enigma’ 25. A recent Indian study found a total thinness prevalence, based on the IOTF criteria, of around 70% in rural Indian schoolchildren 5–12 years of age 26.…”
Section: Discussionmentioning
confidence: 99%
“…This so called Asian Enigma (Ramalingaswami, Jonson, & Rohde, 1997) has spawned substantial research into possible explanations, including gender and intrahousehold biases (Jayachandran & Pande, 2013;Pande, 2003), unusually high rates of open defecation (Spears, 2013;Spears, Ghosh, & Cumming, 2013), genetic predispositions (Nubé, 2009), poor quality diets and food systems (Headey, Chiu, & Kadiyala, 2012), and the inefficacy of nutritional programs and strategies (Das Gupta, Lokshin, Gragnolati, & Ivaschenko, 2005;World Bank, 2005b).…”
Section: Introductionmentioning
confidence: 99%